2013
DOI: 10.5053/ejobios.2013.7.0.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sucrose and polyethylene glycol on hypericins content in Hypericum adenotrichum

Abstract: Background: Hypericum adenotrichum contain many biologically active compounds, some of which, especially hypericins (hypericin and pseudohypericin), have antidepressant, antimicrobial, antiviral, and antitumor properties. In this paper, we report the effects of osmotic stress on the production of hypericins in H. adenotrichum under in vitro conditions. Osmotic stress is an abiotic elicitor that can alter the physiological and biochemical properties of plants, as well as decrease or increase the concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…[69] Sucrose as an osmotic agent was shown to stimulate hypericins in cultured seedlings of H. adenotrichum with increasing concentrations until 45 g/ l, followed by decline. [89] Correspondingly, the presence of saccharose (10-30 g/l) influenced the production of hypericin and hyperforin in H. perforatum shoot cultures and a combination of PEG (1.25-5 g/l) and saccharose (10-30 g/l) synergistically increased the production of the above compounds. [69] Hypericum perforatum cell suspension cultures accumulated anthocyanins and flavonoids with concomitant reduction of xanthones upon increasing the irradiance of cultures from 20 lmol/s per m 2 to 60 lmol/s per m 2 .…”
Section: Physical Factorsmentioning
confidence: 89%
See 3 more Smart Citations
“…[69] Sucrose as an osmotic agent was shown to stimulate hypericins in cultured seedlings of H. adenotrichum with increasing concentrations until 45 g/ l, followed by decline. [89] Correspondingly, the presence of saccharose (10-30 g/l) influenced the production of hypericin and hyperforin in H. perforatum shoot cultures and a combination of PEG (1.25-5 g/l) and saccharose (10-30 g/l) synergistically increased the production of the above compounds. [69] Hypericum perforatum cell suspension cultures accumulated anthocyanins and flavonoids with concomitant reduction of xanthones upon increasing the irradiance of cultures from 20 lmol/s per m 2 to 60 lmol/s per m 2 .…”
Section: Physical Factorsmentioning
confidence: 89%
“…Treatment with polyethylene glycol (PEG) increased the hypericin and pseudohypericin concentrations in cultured H. adenotrichum seedlings. However, this increase was dependent on the concentration of PEG and the treatment period, 10 g/l PEG for a 15‐day treatment being optimal . On the other hand, synthesis of hypericin and hyperforin in H. perforatum shoot cultures was not increased in the presence of 10 and 15 g/l PEG, although a lower PEG concentration stimulated the production of those compounds .…”
Section: Manipulation Of Hypericum Perforatum Secondary Metabolism VImentioning
confidence: 91%
See 2 more Smart Citations
“…Hypericum adenotrichum Spach is a perennial herbaceous and endemic plant, which grows in Turkey. Species-related studies are focused on the identification of the chemical and pharmacological properties and the determination of the secondary metabolite content [10][11][12][13][14]. Within the literature research, it is not found any information about the in vitro germination and seedling development of H. adenotrichum.…”
Section: Introductionmentioning
confidence: 99%